2022
DOI: 10.1021/acsami.1c24909
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Effect of La Doping and Structural Engineering to Achieve Oxygen-Deficient TiNb2O7 for Ultrafast Li-Ion Storage

Abstract: TiNb 2 O 7 (TNO) is a competitive candidate of a fastcharging anode due to its high specific capacity. However, the insulator nature seriously hinders its rate performance. Herein, the La 3+ -doped mesoporous TiNb 2 O 7 materials (La−M−TNO) were first synthesized via a facile one-step solvothermal method with the assistance of polyvinyl pyrrolidone (PVP). The synergic effect of La 3+ doping and the mesoporous structure enables a dual improvement on the electronic conductivity and ionic diffusion coefficient, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…44 Moreover, the R ct in the two electrolytes (Figure S6) was investigated by EIS spectra and showed that can be expressed as eq 1. 12,20 The peak of R 2 is attributed to the Li x Fe(O 1−n P n )F conversion to Fe 0 and LiF, and the reaction process is outlined in eqs 2 and 3. 16 The whole process of the first discharge can be described as eq 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Moreover, the R ct in the two electrolytes (Figure S6) was investigated by EIS spectra and showed that can be expressed as eq 1. 12,20 The peak of R 2 is attributed to the Li x Fe(O 1−n P n )F conversion to Fe 0 and LiF, and the reaction process is outlined in eqs 2 and 3. 16 The whole process of the first discharge can be described as eq 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CV curves (Figure d) of the P-F6 electrode show two reduction peaks at ∼2.55 ( R 1 ) and 1.39 V ( R 2 ). The peak of R 1 corresponds to the Li + insertion into Fe­(O 1– n P n )F formation Li x Fe­(O 1– n P n )­F, which can be expressed as eq . , The peak of R 2 is attributed to the Li x Fe­(O 1– n P n )F conversion to Fe 0 and LiF, and the reaction process is outlined in eqs and . The whole process of the first discharge can be described as eq .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to relieve the issues suffered by bulk TiNb 2 O 7 , various strategies have been tried, such as introducing an oxygen vacancy, regulating the morphology, , doping with alien ions, etc. Oxygen vacancy is an intrinsic defect which can trigger lattice distortion and electron concentration improvement .…”
Section: Introductionmentioning
confidence: 99%
“…Elements’ doping differs from morphology regulating in modification mechanism; the former can not only introduce extra energy bands to reduce the band gap but also increase the crystal lattice parameter to facilitate ion migration. From previous literature, various dopants have been incorporated into bulk TNO, including Tb 4+ , V 5+ , W 6+ , and La 3+ , and the modified electrode materials displayed bigger Li + diffusion coefficients. Taking into account the structural distortion after doping, the ion radius of heteroatoms should be slightly larger than the Ti 4+ ion (0.53 Å) and Nb 5+ ion (0.69 Å).…”
Section: Introductionmentioning
confidence: 99%